Effect of Cracks on the Natural Frequency of Cylindrical Shell Structures - Marwah . Husain; Mohsin Al-shammari (Engineering and Technology Journal, 2020)
Shell structures are liable to different kinds of defects and damage like cracking and corrosion which may destroy their structural safety and affect the service life. The cracks' effects are significant considerations in the design of cylindrical shell structures as they influence the vibration characteristics and safety. This present work is an experimental study on the free vibration analysis of a cylindrical shell involving circumferential surface crack. The influence of the ratio of shell’s radius to a shell’s thickness (R/h)of the shell structure, crack length in the shell, crack depth in the shell, crack location of the shell, and crack orientation in the shell are investigated under a clamped - clamped and simply supported boundary conditions at each end in the shell. Results showed that the minimum impact of the crack is at the angle of crack 75, and the circumferential fissure has more effect than a longitudinal fissure, In addition to this, under SS-SS, C-C the natural frequency will decrease if the fissure is located in the middle of the shell is greater than other locations. but when crack animated across in the ends of the limits the decrease in the natural frequency under C-C only. Results were compared with the literature there was a close agreement.